Pembuatan Teh Herbal Dari Daun Sukun (Artocarpus Altilis) dan Bunga Melati (Jasminum Sambac) - Humairah, Amanda; Putra, Alfian; Nahar, Nahar (Jurnal Riset, Inovasi, Teknologi & Terapan, 2024)
Herbal tea is a mixture of flowers, leaves, seeds, roots, or dried fruits used as a medicinal drink. Breadfruit leaf jasmine flower herbal tea is an herbal drink made in the form of tea powder using breadfruit leaves jasmine flowers which have many benefits including, Lowering cholesterol levels, lowering high blood pressure, kidney failure, treating heart disease, stomach acid, diabetes. Herbal tea makers use variations of the withering process for (4 days, 5 days, and 6 days) and the drying method using an oven for 10 minutes at a temperature of 75 ℃. The tests carried out include yield tests, water content, ash content, antioxidant activity tests using the DPPH method, tannin tests, flavonoids and organoleptic tests. The results showed the best herbal tea at 6 days of withering and compared its composition with sample 3 (TH3). The yield obtained was very low, although there was a reduction in raw materials to the product, the quality of the tea was the best because the air obtained was in accordance with the provisions of SNI No. 3.4%. 3836. 2013 and knowing the quality of life of herbal tea which was 10.6%. antioxidants contained in herbal tea breadfruit leaves have strong antioxidant content, has been proven in the IC50 equation as much as 4.865 in accordance with the provisions of less than 50 indicating the amount of antioxidant content In herbal tea made from jasmine leaves and flowers, the tannin content is 112 mg / kg body weight per day. Testing of flavonoid samples changed color to yellow which indicates positive flavonoids in herbal breadfruit jasmine leaves.